2021
DOI: 10.1111/cpr.13027
|View full text |Cite
|
Sign up to set email alerts
|

Adult neurogenic process in the subventricular zone‐olfactory bulb system is regulated by Tau protein under prolonged stress

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 85 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…Further, the observation that the treatment of depression by antidepressants depends on an increased rate of neurogenesis also corroborates the key role of adult neurogenesis on this type of neurological disorder [ 59 ]. Although the majority of studies reporting a role for adult neurogenesis and stress resilience have been performed in hippocampal neurogenic niches, it has been already shown that the adult SVZ neurogenic process is also compromised under unpredicted prolonged stress [ 60 , 61 ]. Curiously, it has been recently demonstrated that both anxiety- and depression-like states lead to marked olfactory deficits along with impaired adult neurogenesis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the observation that the treatment of depression by antidepressants depends on an increased rate of neurogenesis also corroborates the key role of adult neurogenesis on this type of neurological disorder [ 59 ]. Although the majority of studies reporting a role for adult neurogenesis and stress resilience have been performed in hippocampal neurogenic niches, it has been already shown that the adult SVZ neurogenic process is also compromised under unpredicted prolonged stress [ 60 , 61 ]. Curiously, it has been recently demonstrated that both anxiety- and depression-like states lead to marked olfactory deficits along with impaired adult neurogenesis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tauopathy mice showed a decrease in the proliferation of adult NSCs in the SVZ from 2 months of age ( Komuro et al, 2015 ). Although tau plays a key role in the impairment of SVZ neuronal proliferation and migration under conditions such as chronic stress ( Dioli et al, 2021 ), its effect on adult SVZ neurogenesis in AD remains unclear. Finally, dysfunction of subependymal lipid metabolism plays a critical role in the deficits of adult SVZ neurogenesis in the early stage of AD via hyperactivation of the protein kinase B signaling pathway ( Gontier et al, 2015 ; Scopa et al, 2020 ).…”
Section: Subventricular Zone Neurogenesis In Alzheimer’s Diseasementioning
confidence: 99%
“…Protection in tau-KO mice is associated with reduced neuronal excitability [ 47 , 48 ], albeit long-term hippocampal potentiation and long-term depression are variable depending on the tau-KO strain [ 49 , 50 , 51 ]. The role of tau is also manifested in the modulation of adult neurogenesis in the hippocampus, olfactory bulb, and subventricular region under prolonged stress [ 52 , 53 ]. Tau deletion also prevents stress-induced dendritic atrophy [ 54 ].…”
Section: Introductionmentioning
confidence: 99%